Job–education mismatch and wage penalties: Evidence from graduates in educational science and teacher education in Vietnam - Nguyen, Thanh; Nguyen, Anh; Tran, Anh; Vu, Lien; Lu, Oanh (Journal of Interdisciplinary Studies in Education, 2026)
This paper examines education–job mismatch and wage differences among graduates in educational science and teacher education in Vietnam. We analyse wage effects of field-of-study mismatch and full mismatch, defined as the joint occurrence of overeducation and field mismatch. Contrary to much existing evidence, field-of-study mismatch is associated with a wage premium, particularly among women, older workers, and private-sector workers. For some graduates, working outside education yields higher earnings than remaining in teaching-related jobs. In contrast, full mismatch is consistently linked to wage penalties, with larger disadvantages for younger graduates, women, private-sector employees, and rural workers. The findings point to a clear paradox: teaching retains social prestige, yet low pay may weaken retention and encourage graduates to leave the sector.